Hubungan Penghargaan Kendiri dan Kemurungan ke atas Pencapaian Akademik Pelajar Tingkatan Empat - Khairul Bariyah, Kassim (2003)
The main purpose of this study was to investigate the relationship between self-esteem, depression and students’ achievement. It also sought to examine gender differences in self-esteem and depression. The participants in this study comprised 200 Form four students from four different schools namely SMK Bachok, SMK Badak, SMK Jelawat and SMK (A) Tangok. To measure these psychological constructs, two instruments were used: Children Depression Inventory (CDI) and Self-Esteem Inventory (SEI). Data analysis was based on Pearson correlation, t-test, and regression. The results showed significant positive correlation between self-esteem and academic achievement. Findings also indicated an inverse relationship between depression and academic achievement, and also self-esteem and depression. High depression is associated with both low self-esteem and low academic achievement. The findings also indicated that males and females showed no significant difference in their level of self-esteem and depression. This study also found that depression was a more significant predictor of academic achievement compared to self-esteem.